1997
DOI: 10.1097/00005537-199704000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐67 As a Prognostic Marker in Adenoid Cystic Carcinoma Assessed With the Monoclonal Antibody MIB1 in Paraffin Sections

Abstract: The monoclonal antibody MIB1 recognizing the Ki-67 antigen in formalin-fixed, paraffin-embedded tissue was used to study the proliferative activity in 44 adenoid cystic carcinomas of the salivary glands. The antigen expression was compared with clinical factors, histopathological grading, and prognosis. The Ki-67 value was significantly higher in tumors from patients suffering from treatment failure than in nonfailures (P<0.001). The Ki-67 expression was also higher in tumors exhibiting areas more than 30% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 24 publications
6
39
1
2
Order By: Relevance
“…However in accordance with our study ,in all of these studies the frequency of Ki67 expression was lower in benign tumor in comparison with malignant tumors and lower in ACC than MEC (Hollstein et al, 1991;Nordgard et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…However in accordance with our study ,in all of these studies the frequency of Ki67 expression was lower in benign tumor in comparison with malignant tumors and lower in ACC than MEC (Hollstein et al, 1991;Nordgard et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…Using a cutoff of 5 % or higher, there was no statistically significant difference in outcome for those with a high proliferation index versus those with a low proliferation index: mean 8.2 versus 10.5 years, respectively; and 64.3 versus 53.6 % dead of disease, respectively. This is different from others who have reported a statistically significant difference [76,77,105]. However, an increased ki-67 index is noted in pleomorphic adenoma that undergo malignant transformation to ACC ex-pleomorphic adenoma [105,145,146].…”
Section: Immunohistochemical Studiescontrasting
confidence: 91%
“…It has to be emphasized in this context, that no valid reference system defining low or high levels of Ki-67 expression in salivary gland tumors has been established so far. 5,6 For statistical analysis, the results of Ki-67 staining were, therefore, classified by the authors through quantitative scoring in 3 grades (Grade 1, 1-25% stained cells; Grade 2, 26 -50% stained cells; Grade 3, Ͼ 50% stained cells).…”
Section: Methodsmentioning
confidence: 99%
“…Giannoni et al 6 reported that benign tumors in the minor salivary glands commonly showed a proliferation rate Ͻ 12%. However, Norgard et al 5 described a significantly higher rate of recurrent disease in patients with adenoid cystic carcinoma, with a proliferation rate (Ki-67) Ͼ 4%. In the current study, 73.5% of the patients showed a proliferation rate Ͼ 25%, with an average proliferation rate of 34.8%, which within this context has to be interpreted as being very high.…”
Section: Table 4 Prognostically Significant Factors In Sdc Clinical Cmentioning
confidence: 99%
See 1 more Smart Citation